The bio-politics of the developmentalist Francoism: toward a new form of government (1959-1975) - Cayuela Sánchez, Salvador (Revista de Filosofía, 2013)
In this article I want to show the characteristic elements of the bio-politics in the developmentalist Francoism, from 1959 to 1975. For this, I will distinguish three fields of study – economic, health and the ideological – and I will analyze the most characteristic – disciplinaries and regulatories – bio-political devices for each of them. At the same time, the analysis of these devices will allow me to show the most distinctive elements of the governmentality of the last Francoism, understanding this concept as “conduct of conducts” tried out by the Franco’s regime in this period. Finally, all of this will allow me to provide a new interpretation about the end of the Franco’s regime, indicating the effectiveness of its bio-political devices, and announce the birth of a new governmentality in Spain with the democracy arrival.
Keywords: bio-political; developmentalist Francoism; gouvernmentality; subjectivity; bio-political devices.